2020
DOI: 10.1186/s12964-019-0506-4
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the PDGFRα-Nrf2 pathway mediates impaired adipocyte differentiation in bone marrow mesenchymal stem cells lacking Nck1

Abstract: Background: The limited options to treat obesity and its complications result from an incomplete understanding of the underlying molecular mechanisms regulating white adipose tissue development, including adipocyte hypertrophy (increase in size) and hyperplasia (increase in number through adipogenesis). We recently demonstrated that lack of the adaptor protein Nck1 in mice is associated with reduced adiposity and impaired adipocyte differentiation. In agreement, Nck1 depletion in 3 T3-L1 cells also attenuates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Nrf2 also plays an important role in adipogenesis ( Haider & Larose 2020 ). In previous studies, we observed that overexpression of asprosin could reduce the expression of Nrf2, inhibit its activity and downregulate its downstream target genes.…”
Section: Resultsmentioning
confidence: 99%
“…Nrf2 also plays an important role in adipogenesis ( Haider & Larose 2020 ). In previous studies, we observed that overexpression of asprosin could reduce the expression of Nrf2, inhibit its activity and downregulate its downstream target genes.…”
Section: Resultsmentioning
confidence: 99%
“…To further confirm the adipogenic lineage, we investigated the gene expression level of adiponectin [53], leptin [54], and PPARg [55], which were found to be associated with the promotion of adipogenic differentiation. The mRNA fold change of these adipogenic genes were calculated and normalized to cyclophilin B gene by 2 -ΔΔCT method [56,57]. All the gene expression levels increased for hASCs cultured for 9 days in adipogenic media compared to 6 days culture.…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant protein expression is regulated mainly by the Nrf2/Keap1 pathway [ 13 , 14 , 15 ], which could be initiated by the activation of PDGFRα [ 13 ]. In our conditions, HG seemed to induce the expression of the Nrf2 gene ( Figure 5 A), which could have been related to a compensatory mechanism and a cell-specific antioxidant response [ 16 , 51 ]; similarly, HG increased the Keap1 gene expression at 9 h ( Figure 5 B), which is known for retaining Nrf2 in the cytoplasm [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the Nrf2/Keap1 pathway is the primary regulator of antioxidant enzyme expression [ 12 ]. The Nrf2/Keap1 pathway is activated by increased ROS production, which leads to Keap1 oxidation and consequently Nrf2 release and translocation from cytoplasm to the nucleus, where it acts as a transcription factor for antioxidant enzymes [ 13 , 14 , 15 ]. However, the response of Nrf2 under conditions of metabolic stress is weak [ 16 ], so molecules that upregulate this pathway may improve endothelial function in diabetes.…”
Section: Introductionmentioning
confidence: 99%